2018
DOI: 10.3171/2017.1.jns161243
|View full text |Cite
|
Sign up to set email alerts
|

“Birdlime” technique using TachoSil tissue sealing sheet soaked with fibrin glue for sutureless vessel transposition in microvascular decompression: operative technique and nuances

Abstract: OBJECTIVE Microvascular decompression (MVD) is effective for the treatment of trigeminal neuralgia (TN), hemifacial spasm (HFS), and glossopharyngeal neuralgia. The transposition technique is the standard procedure to avoid adhesions and granuloma around the decompression site but is more complex and difficult to perform than the interposition technique. The authors describe a simple and safe MVD transposition procedure they call the "birdlime" technique, which uses a tissue glue-coated collagen sponge soaked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…3) Therefore, it is desirable to pull the causative vein together with the surrounding arachnoid and stuck the arachnoid and petrosal dura by the Birdlime technique. 13) In our Case 1, slight symptoms persisted after treatment; however, it is unknown whether this was due to nerve injury associated with surgical manipulation or repeated nerve block. Thus, the treatment of venous TN is far more difficult than that of arterial TN in terms of curability.…”
Section: Discussionmentioning
confidence: 58%
“…3) Therefore, it is desirable to pull the causative vein together with the surrounding arachnoid and stuck the arachnoid and petrosal dura by the Birdlime technique. 13) In our Case 1, slight symptoms persisted after treatment; however, it is unknown whether this was due to nerve injury associated with surgical manipulation or repeated nerve block. Thus, the treatment of venous TN is far more difficult than that of arterial TN in terms of curability.…”
Section: Discussionmentioning
confidence: 58%
“…22 The safety of intradural use of TachoSil ® has not been fully examined, but no adverse effect has been reported. 8,23 Hearing loss remains a significant risk with MVD especially for HFS. 24 A systematic review showed that the incidences of hearing loss after MVD for HFS and TN were 8.25% and 5.58%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…surgical glue or other surgical products, such as tachosil, have recently been used instead of suturing due to the complexity of this surgical technique [ 1 , 45 , 46 ]. these studies have been recently published, and although the initial effect is acceptable, the durability is controversial because there is not enough follow-up.…”
Section: Decompression Techniquementioning
confidence: 99%